MEAN SEA-LEVEL OBSERVED AT SYOWA STATION, EAST ANTARCTICA - オダマキ, ミノル; ミチダ, ユタカ; ノグチ, イワオ; イワナガ, ヨシユキ; イケダ, シュンイチ; イワモト, コウジ; ODAMAKI, Minoru; MICHIDA, Yutaka; NOGUCHI, Iwao; IWANAGA, Yoshiyuki; IKEDA, Shunichi; IWAMOTO, Koji (National Institute of Polar Research, 1991)
P(論文) Hydrographic Department of Maritime Safety Agency, Japan, has continued tidal observation at Syowa Station as part of the Japanese Antarctic Research Expedition project since 1966. The tidal observation system and data processing manner are described in this paper. Using the well-controlled data from 1981 to 1987,monthly mean sea-levels are analyzed and show the trend of the falling at the rate of about 1cm/year. Furthermore, it is also shown that the seasonal change of mean sea-level at Syowa Station is larger than those at other stations around the Antarctic Sea. departmental bulletin paper